2014
DOI: 10.1590/s1517-83822014000300024
|View full text |Cite
|
Sign up to set email alerts
|

A method to estimate the biomass of Spirulina platensis cultivated on a solid medium

Abstract: This paper presents a method to estimate the biomass of Spirulina cultivated on solid medium with sugarcane bagasse as a support, in view of the difficulty in determining biomass concentrations in bioprocesses, particularly those conducted in semi-solid or solid media. The genus Spirulina of the family Oscillatoriaceae comprises the group of multicellular filamentous cyanobacteria (blue-green microalgae). Spirulina is used as fish feed in aquaculture, as a food supplement, a source of vitamins, pigments, antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…The protein content in the initial day was 36% and it was 72% and 39% on day 4 and 6, respectively (Figure 6) The protein content of the Spirulina increased as the biomass increased, and vice versa, suggesting that the biomass and the protein content are directly proportional to each other. These findings are consistent with previous reports [42]. The studies of McCarty, (2007) showed that, C-phycocyanin contains phycocyanobilin, and it is the major protein present in Spirulina and accounts for about 20% of algae's dry weight [43].…”
Section: Protein Estimation By the Lowry Methodssupporting
confidence: 92%
“…The protein content in the initial day was 36% and it was 72% and 39% on day 4 and 6, respectively (Figure 6) The protein content of the Spirulina increased as the biomass increased, and vice versa, suggesting that the biomass and the protein content are directly proportional to each other. These findings are consistent with previous reports [42]. The studies of McCarty, (2007) showed that, C-phycocyanin contains phycocyanobilin, and it is the major protein present in Spirulina and accounts for about 20% of algae's dry weight [43].…”
Section: Protein Estimation By the Lowry Methodssupporting
confidence: 92%
“…Sugar cane bagasse in a solid‐state medium mixed with Paoletti’s medium was a known combined medium even before the Zarrouk’s medium was formulated (Pelizer & Moraes 2014). The biomass was estimated from the protein content acquired from the surface growth of the microalgae after washing, filtration and drying.…”
Section: Alternatives To Zarrouk’s Medium: Research Trendsmentioning
confidence: 99%
“…The cultures were started with inocula previously acclimated to the mentioned environmental conditions. From the beginning of the test and every 48 h, samples were taken from each of the replicas to determine the pH and population growth according to the criteria of Pelizer and Oliveira (2014).…”
Section: Methodsmentioning
confidence: 99%